Synthesis and evaluation of novel dapsone-thalidomide hybrids for the treatment of type 2 leprosy reactions - Yamasaki, Paulo Renato [UNESP]; Nascimento, Dejair Caetano do; Chelucci, Rafael Consolin [UNESP]; Belone, Andrea de Faria Fernandes; Rosa, Patricia Sammarco; Diorio, Suzana Madeira; Melo, Thais Regina Ferreira de [UNESP]; Barbieri, Karina Pereira [UNESP]; Polesi Placeres, Marisa Campos [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Chin, Chung Man [UNESP]; Santos, Jean Leandro dos [UNESP] (Elsevier B.V., 2014)
We synthesized a series of novel dapsone-thalidomide hybrids (3a-i) by molecular hybridization and evaluated their potential for the treatment of type 2 leprosy reactions. All of the compounds had analgesic properties. Compounds 3c and 3h were the most active antinociceptive compounds and reduced acetic acid-induced abdominal constrictions by 49.8% and 39.1%, respectively. The hybrid compounds also reduced tumor necrosis factor-alpha levels in lipopolysaccharide-stimulated L929 cells. Compound 3i was the most active compound; at concentrations of 15.62 and 125 mu M, compound 3i decreased tumor necrosis factor-alpha levels by 86.33% and 87.80%, respectively. In nude mice infected with Mycobacterium leprae in vivo, compound 3i did not reduce the number of bacilli compared with controls. Compound 3i did not have mutagenic effects in Salmonella typhimurium strains TA100 and TA102, with or without metabolic activation (S9 mixture). Our results indicate that compound 3i is a novel lead compound for the treatment of type 2 leprosy reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Leprosy; M. leprae; Anti-inflammatory; Analgesic; TNF alpha; Dapsone; Thalidomide; Molecular hybridization; Erythema nodosum leprosum